Ultrasonographic Transabdominal Measurement of Uterine Cervical Length for the Prediction of a Midtrimester Short Cervix - Guerby, Paul; Beaudoin, Annie; Marcoux, Geneviève; Girard, Mario; Pasquier, Jean-Charles; Bujold, Emmanuel (American Journal of Perinatology, 2020)
Objective This study was aimed to estimate the value of transabdominal (TA) ultrasound measurement of cervical length (CL), as an alternative of transvaginal (TV) ultrasound, for universal screening of short cervix in the midtrimester.Study Design We conducted a prospective cohort study of nulliparous women with singleton pregnancy at 20 to 24 weeks of gestation. All participants underwent TA ultrasound followed by TV ultrasound with acquisitions of images and videos of the uterine cervix. A second sonographer, blinded to the participants' data and pregnancy outcomes, measured the CL using TA and TV images and videos. Pearson's correlation test and receiver operating characteristic (ROC) curve analyses were performed.Results A total of 805 participants were recruited, including 780 (97%) where TA CL measurement was feasible. We observed a strong correlation of CL between TA and TV (correlation coefficient: 0.57; p < 0.0001) with a mean TA measurement being 4 mm (95% confidence interval [CI]: −6 to 14 mm) below the mean TV measurement (mean of differences: 5 ± 4 mm). We observed that a TA CL <30 mm was highly predictive of a short cervix defined as a TV CL ≤25 mm (area under the ROC curve: 0.97; 95% CI: 0.95–0.99; p < 0.0001) with a sensitivity of 100% and a false-positive rate of 22%.Conclusion Universal short cervix screening in nulliparous women could be performed using TA ultrasound, which could allow the avoidance of TV ultrasound in more than three quarter of women. In low-risk population, TV ultrasound could be reserved to women with TA CL <30 mm.Key Points
Keywords: cervical length screening; transabdominal ultrasound; preterm birth prediction; short cervix